Current Principles and Practices of Telemedicine and e-Health - Latifi, Rifat (IOS Press, 2013)
This book represents the most current developments in the rapidly expanding and changing field of telemedicine and e-health, especially in the developing countries. Much has changed since the publication of the first book in 2004 (Establishing Telemedicine in Developing Countries: From Inception to Implementation). Telemedicine has become more popular, and continues to grow. Over the last three years, I have received many requests for copies of the book from all over the world. While there are many good books and materials on telemedicine, my hope is that this one will become a useful reference for all of those practicing telemedicine and e-health, particularly in developing countries. It is dedicated to all future generations of telemedicine and e-health students, including health care practitioners, administrators, policy makers, technical professionals and others.